Unlocking Math Skills: The Argeo Math App for Enhanced Mathematical Problem-Solving - Hidayati, Yulia Maftuhah; Kusuma, Anton Adi Suryo; Wibosono, Muhammad Exsel Wimpy; Safitri, Sylviana Ika (Universitas Muhammadiyah Surakarta, 2023)
This study aimed to design and evaluate the effectiveness of